Future of the world bank - Reid, Escott (Washington, 1965)
The term, World Bank, is used in two senses. In one sense it means the World Bank proper, the inter national institution which was born at the Bretton Woods Conference in 1944 at the same time as the International Monetary Fund, which started operat ing in 1946 and which has a membership of 102 governments. In another sense it means the World Bank group of institutions which includes, in addi tion to the World Bank proper, the two offsprings of the World Bank, the International Finance Corpo ration (IFC), founded in 1956 to provide funds for private projects in the underdeveloped countries without government guarantee, and the Interna tional Development Association (IDA), founded in 1960 to provide loans on soft financial terms.